Interface rupture of thin film on the cooling substrate - Tan, Sherlyn ShiHui (2016)
Thin film rupture plays a big role in industrial applications such as coating, cleaning and lubrication. This report first explores the possibility of observing rupture occurrences under horizontal temperature gradient. It was done by heating two uncoated wires (in the shape of two concentric circles with different diameters and affixed onto substrate) at different voltages, and with ethanol between the two circles. No rupture was observed as ethanol was found to be receding only. The vertical temperature gradient was created by the temperature difference between the substrate placed on the hollow metal block (cooled using a circulator), and the surrounding. Analysis of the data revealed that the method of sliding the working fluid across the substrate (to generate thin film) yielded more accurate results than the method of holding two substrates together and sliding one away. General trend analysis of experimental results agreed that as temperature increased, the average time taken for the rupture to attain a certain size decreased while the average number of rupture regions increased. The average number of rupture regions on the hydrophobic Poly(methyl methacrylate) (PMMA) for all temperatures were found to be higher than those on the hydrophilic microscopic glass. Thus, it suggests that a substrate with lower wettability promotes rupture more than one with higher wettability. The decrease in average number of rupture region as temperature decreased was explained by the Marangoni effect. Rupture formation was prevented as surrounding ethanol of a lower surface tension was encouraged to fill in the depressed region of a higher surface tension. Future work is recommended to focus on the vertical temperature gradient and to make use of the confocal optical sensor to accurately determine the film thickness and its changes as the rupture occurs. Lastly, a literature review on thermocapillary flow has led to the design of a circular chamber to overcome design flaws in past studies and to be the basis of future study of the thermocapillary convection and its associated instabilities in thin film evaporation.